2020
DOI: 10.1016/j.bbr.2019.112302
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dopamine and serotonin synthesis inhibitors on the ketamine-, d-amphetamine-, and cocaine-induced locomotor activity of preweanling and adolescent rats: sex differences

Abstract: The pattern of ketamine-induced locomotor activity varies substantially across ontogeny and according to sex. Although ketamine is classified as an NMDA channel blocker, it appears to stimulate the locomotor activity of both male and female rats via a monoaminergic mechanism. To more precisely determine the neural mechanisms underlying ketamine's actions, male and female preweanling and adolescent rats were pretreated with vehicle, the dopamine (DA) synthesis inhibitor ∝-methyl-DL-p-tyrosine (AMPT), or the ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 115 publications
0
5
0
Order By: Relevance
“…Researches in animal models had also shown that 5-HT is positively correlated with PRL (47). There were evidences demonstrated that agonists of 5-HT could induce erection in animal models and the antagonists could prevent the dopamine (DA)-induced erection (48). In summary, the relationship between low PRL and ED could be explained by a reduction of central 5-HT.…”
Section: Discussionmentioning
confidence: 94%
“…Researches in animal models had also shown that 5-HT is positively correlated with PRL (47). There were evidences demonstrated that agonists of 5-HT could induce erection in animal models and the antagonists could prevent the dopamine (DA)-induced erection (48). In summary, the relationship between low PRL and ED could be explained by a reduction of central 5-HT.…”
Section: Discussionmentioning
confidence: 94%
“…It is possible that ketamine-induced locomotor activity stimulation in female rats could be due to enhanced dissociative stereotypy, such as ataxia, when compared to that of male rats [ 42 ]. In addition, sex differences in the pharmacokinetic or monoaminergic activity of ketamine [ 58 ] may have contributed to enhanced locomotor stimulation in female rats. These results demonstrate that female rats exhibit greater sensitivity to locomotor stimulatory effects of ketamine at dissociative doses.…”
Section: Discussionmentioning
confidence: 99%
“…These doses of cocaine and D -amphetamine were chosen because they produce substantial locomotor activity in all age groups tested [52][53][54][55]. In the companion paper to this study [56], the locomotor activating effects of ketamine, cocaine, and D -amphetamine were assessed in male and female rats pretreated with selective DA and 5-HT synthesis inhibitors.…”
Section: Introductionmentioning
confidence: 99%